2007
DOI: 10.1007/s10792-007-9069-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial keratitis in West Anatolia, Turkey: a retrospective review

Abstract: Staphylococci are the most commonly isolated microbial agents in cases of infectious keratitis in West Anatolia, Turkey. These findings will provide valuable background information and facilitate successful treatment in this region, and they will be useful as reference data for the particular population in this region as a basis for empirical antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 31 publications
4
25
1
1
Order By: Relevance
“…Among the bacteria isolated, Gram-positive cocci continue to be the most frequent agent, with a similar rate compared to the other studies in both elderly and age-independent series (17,20,26,(28)(29)(32)(33)(34)(35)(38)(39)(40)(41)(42)(43) . The incidence of Gram-negative bacilli was a little higher, which could be explained by geographical variation in the microbial flora of our patients (2,(14)(15)44) .…”
Section: Microbiologysupporting
confidence: 71%
See 2 more Smart Citations
“…Among the bacteria isolated, Gram-positive cocci continue to be the most frequent agent, with a similar rate compared to the other studies in both elderly and age-independent series (17,20,26,(28)(29)(32)(33)(34)(35)(38)(39)(40)(41)(42)(43) . The incidence of Gram-negative bacilli was a little higher, which could be explained by geographical variation in the microbial flora of our patients (2,(14)(15)44) .…”
Section: Microbiologysupporting
confidence: 71%
“…The prevalence of ocular trauma varied considerably among the studies on the elderly, from 3.7 to 43.6% (17,26,(28)(29) , but was relatively constant in the age-independent series, ranging from 16 to 26.6% (32)(33)(34)(35) . Contact lens wear was found in only 3.0% of cases, like the already mentioned studies with the exception of van der Meulen et al (29) , which found 13.0%.…”
Section: Predisposing Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…The resistance of Pseudomonas to disinfectants, coupled with its adherence capability to plastics, facilitates its introduction into the eye where it can react with defective corneal epithelium, gaining further entrance into the corneal stroma. S. pneumonia on the other hand is the major cause of corneal ulcers in developing countries however, some reports emphasize on the fact that Streptococcus are most commonly encountered after P. aeruginosa and/or S. aureus eye infections [14,114,215]. Unlike P. aeruginosa, pneumococcal keratitis is not commonly associated with the use of contact lenses and the predisposing factors often include ocular trauma or surgery [31,104,114,125,160,207].…”
Section: Bacterial Keratitismentioning
confidence: 99%
“…Therefore, timely antimicrobial treatment must be initiated for rapid eradication of the infecting organism. Numerous reports from all over the world indicate a methicillin-resistance rate of up to 74% among S. aureus isolates, which emphasizes the necessity to search for new anti-S. aureus agents as an alternative to currently available antibiotics [2][3][4][5][6]. Enzyme-based therapy has been proposed as an alternative approach to treatment with antibiotics.…”
Section: Introductionmentioning
confidence: 99%